(untitled) (Sebha University Conference Proceedings, 2025)
This study aims to provide a comprehensive analysis of the concept of Embodied Energy and its central importance in evaluating the sustainability of materials and construction projects within the building sector. Embodied energy is defined as the total energy consumed across the entire lifecycle of a material. This includes raw material extraction, processing, manufacturing, transportation, installation, maintenance, and ultimately, end-of-life considerations (recycling or disposal). The study highlights that embodied energy can represent over 50% of a building’s total lifecycle energy consumption, particularly in structures with high operational efficiency. By adopting a Life Cycle Assessment (LCA) methodology, informed design decisions can be made. The study presents analytical data for the embodied energy of common building materials, demonstrating significant variation. Materials such as aluminum and steel show high values compared to concrete and wood. A case study of a residential building in Libya is included, comparing a structural frame system with a load-bearing wall system. The load-bearing wall system demonstrates approximately 18% lower embodied energy. The findings emphasize the importance of early design choices and recommend the adoption of policies supporting the use of materials and systems with low embodied energy to achieve genuine environmental sustainability in the construction sector.